Govorjeni jezik med raziskovanjem in tehnologijo: Zbornik povzetkov (University of Maribor Press, 2025)
Spoken Language between Research and Technology: Book of Abstracts. The book of abstracts from the conference Spoken Language between Research and Technology brings timely contributions at the intersection of spoken language resources, linguistics, and speech technologies. It features publicly available Croatian child-language corpora in CHILDES/TalkBank and the ParlaSpeech V3 collection. Several papers address the creation and processing of Slovenian speech resources: from citizen-science strategies and open-source tools (alignment, anonymization, validation, normalization) to phonetic transcription in the Digital Dictionary Database of Slovene and the expansion of lexical resources with typically spoken vocabulary. The research spans (dis)fluency and filled-pause detection, the relationship between prosodic and syntactic units, and challenges of dialect transcription; a new EPIC-SI early communication corpus is also announced. The volume is open access under the CC BY-SA license and is intended for researchers in linguistics, corpus studies, and speech technologies, as well as the broader professional community.